2020
DOI: 10.3390/pathogens9120984
|View full text |Cite
|
Sign up to set email alerts
|

Co-Circulation of Two Independent Clades and Persistence of CHIKV-ECSA Genotype during Epidemic Waves in Rio de Janeiro, Southeast Brazil

Abstract: The Chikungunya virus infection in Brazil has raised several concerns due to the rapid dissemination of the virus and its association with several clinical complications. Nevertheless, there is limited information about the genomic epidemiology of CHIKV circulating in Brazil from surveillance studies. Thus, to better understand its dispersion dynamics in Rio de Janeiro (RJ), one of the most affected states during the 2016–2019 epidemic waves, we generated 23 near-complete genomes of CHIKV isolates from two mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…Our phylogenetic analysis placed the genomes to the ECSA genotype. This lineage has been reported as predominant in the Southeast and Northeast Region of Brazil, respectively [ 12 , 36 , 37 , 38 , 39 ]. Naveca et al [ 40 ] reported the introduction of the ECSA lineage in Roraima in the North Region of Brazil, and de Castro et al reported the ESCA circulation in the Paraná state in the South Region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Our phylogenetic analysis placed the genomes to the ECSA genotype. This lineage has been reported as predominant in the Southeast and Northeast Region of Brazil, respectively [ 12 , 36 , 37 , 38 , 39 ]. Naveca et al [ 40 ] reported the introduction of the ECSA lineage in Roraima in the North Region of Brazil, and de Castro et al reported the ESCA circulation in the Paraná state in the South Region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fabri et al (2020), since 2015, two independent CHIKV-ECSA genotype introductions occurred in RJ, both from Brazil's northeastern region [67]. The first report and characterization of CHIKV-ECSA in RJ occurred in 2016 [68].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, given that the ECSA lineage was responsible for the ongoing outbreak at the time of development, the high degree of amino acid similarity between the two CHIKV strains suggested that the vaccine would be protective against viruses of other genotypes. However, it would have been curious to characterize a VLP produced from a CHIKV strain of the ECSA lineage, given that it is the strain responsible for recent Chikungunya epidemics all around the world [ 119 , 120 , 121 , 122 , 123 ].…”
Section: Alphavirus Vaccine Developmentmentioning
confidence: 99%
“…Data curated from literature reported through February 2021. Numbers in superscript refer to reference numbers (See Reference list [ 23 , 73 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ,…”
Section: Figurementioning
confidence: 99%